5(4H)-oxazolones: Synthesis and biological activities. Issue 2 (17th January 2021) - Haneen, David S. A.; Abou-Elmagd, Wael S. I.; Youssef, Ahmed S. A.
Abstract: In this review, we summarize all the synthetic methods and a variety of different techniques which has been used to prepare 4-arylidene-2-subsititued-5(4 H )-oxazolone derivatives followed by a focused survey on the biological importance of this nucleus. Graphical Abstract: